UJI DAYA HAMBAT EKSTRAK KULIT KAYU MANIS TERHADAP PERTUMBUHAN JAMUR TRICHOPHYTON MENTAGROPHYTES SECARA IN VITRO - FIRMANSYAH, REZA; LINGGA, FEBRINA DEWI PRATIWI (JURNAL ILMIAH MAKSITEK, 2024)
Trichophyton mentagrophytes is a type of fungal species that most often causes dermatophyte infections that can cause skin infections. The fungus Trichophyton mentagrophytes often causes skin infections such as tinea. Cinnamon (Cinnamomum burmanni) can be grown in several areas in Indonesia. Cinnamon bark contains chemical compounds, namely flavonoids, alkaloids, saponins, and tannins. To determine the inhibitory power of cinnamon bark extract (Cinnamomum burmannii) in inhibiting the growth of the fungus Trichophyton mentagrophytes. This study was experimental, post test only, consisting of 4 groups: two intervention groups (10% and 20% cinnamon bark extract), positive control (Flucanozole), negative control (aquadest). Five samples have been identified as Tricophyton mentagrophytes. In this test, potato dextrose agar was used and the growth inhibitory effect was determined by measuring the apparent clear zone. The results showed that cinnamon bark extract (Cinnamomum burmannii) with concentrations of 10% and 20% could inhibit the growth of the fungus Trichophyton mentagrophytes. Cinnamon bark extract (Cinnamomun burmannii) with a concentration of 10% and 20% has the ability as an antifungal against the growth of the fungus Trichophyton mentagrophytes. Cinnamon bark extract (Cinnamomun burmannii) with a concentration of 20% was more effective in inhibiting the growth of the fungus Trichophyton mentagrophytes (the highest clear zone) than cinnamon bark extract with a concentration of 10%.